TikTok and Democratic Recession: An Analysis of the Trump and Harris 2024 Campaign - Wilches Tinjacá, Jaime Andrés; Guerrero Sierra, Hugo Fernando; Niño González, César Augusto (Estudios sobre el Mensaje Periodístico, 2025)
The United States presidential elections were characterized by the absence of scenarios representing ideologies in dispute over the orientation of the societal model. Instead, a trend was evident in which apathy towards deliberative democracy and the hyper-personalization of candidates were exacerbated. This article analyzes the impact of TikTok on the described trend through the study of the political campaigns of Donald Trump and Kamala Harris during the 2024 electoral contest. The method uses content analysis based on three dimensions (thematic, technical, and emotional), with a corpus of 406 TikToks published on the official accounts of the candidates and generated by third parties. The results show that TikTok has become a crucial tool for political communication, allowing direct interaction with voters. This does not imply a constant production of communicative pieces but rather transforms influence into the strategic ability to viralize content and project charismatic traits of politicians. The discussion highlights how TikTok has transformed politics into a spectacle, where authenticity and emotional connection prevail over rationality and information verification. The research is novel in providing evidence of TikTok's impact on contemporary democracies and electoral marketing, emphasizing the need for new theories on information manipulation and media literacy in the digital age.
Keywords: TikTok; emotions; democracy; viralization; debate; manipulation